Pola Distribusi Aboveground Biomass Kawasan Hutan Mangrove Peniti Kalimantan Barat - Rafdinal, Rafdinal; Rizalinda, Rizalinda; Minsas, Sukal (Universitas Negeri Semarang, 2019)
This study aims to analyze the distribution pattern of aboveground biomass (AGB) in the mangrove ecosystem of West Kalimantan Safety. In addition, it also analyzes the differences in biomass and carbon stocks in the condition of mangrove forests. The study of the distribution pattern of AGB of mangrove forests was carried out between August and September 2018. Determination of the location of the study was based on a conceptual approach in the dimensions of spatial temporal that is using the Porposive Random Sampling method. Vegetation analysis was carried out by a single plot measuring 50 m x 50 m at each selected location. Based on vegetation analysis data it was found that the density of mangrove stands on the Peniti coast ranged from 38 to 185 ind /ha, with an average of 88.25 Â± 66.15 ind./ Ha. The AGB of pinch mangrove forests ranged from 8.85 to 84.82 Mg / ha with the largest total AGB distributed in the stand diameter class of more than 80 cm. Penelitian ini bertujuan untuk menganalisis pola distribusi aboveground biomass (AGB) pada ekosistem mangrove Peniti Kalimantan Barat. Selain itu juga untuk menganalisis perbedaan biomassa, dan cadangan karbon pada kondisi hutan mangrove. Kajian pola distribusi AGB hutan mangrove Peniti dilakukan antara bulan Agustus dan September 2018. Penentuan lokasi penelitian didasarkan pada pendekatan konseptual dalam dimensi spasio temporal yaitu menggunakan metode Porposive Random Sampling. Analisis vegetasi dilakukan dengan metode petak tunggal berukuran 50 m x 50 m pada setiap lokasi terpilih. Berdasarkan data analisis vegetasi didapatkan bahwa kerapatan tegakan mangrove di pesisir Peniti berkisar antara 38 sampai 185 ind/ha, dengan rata-rata 88,25Â±66,15 ind./ha. AGB tegakan hutan mangrove Peniti berkisar antara 8,85 sampai 84,82 Mg/ha dengan total AGB terbesar terdistribusi pada kelas diameter tegakan lebih dari 80 cm.